Risk assessment of dietary exposure to phytosterol oxidation products from baked food in China. Issue 2 (1st February 2018) - Hu, Yinzhou; Wang, Mengmeng; Huang, Weisu; Yang, Guoliang; Lou, Tiantian; Lai, Shiyun; Lu, Baiyi; Zheng, Lufei
ABSTRACT: Phytosterols are nutritional phytochemicals that may undergo oxidation and be transformed into phytosterol oxidation products (POPs), thus inducing pathological and toxic effects. This work investigated four main phytosterols and 28 POPs in 104 kinds of commercial baked food by using GC-MS. The dietary exposure and hazard index values (HI) associated with POPs from baked food consumption in China were estimated by using Monte Carlo simulation. Concentrations of the total phytosterols were between 3.39 and 209.80 μg/g. The total concentrations of POPs, including 5α, 6α/5β, 6β-epoxysterols, 7-ketosterol, 7α/7β-hydroxysterols, 6-hydroxysterols, and triols, ranged from 0.37 to 27.81 μg/g. The median dietary exposure of POP contents in baked food for four age groups in China were 10.91 (children), 6.20 (adolescents), 3.63 (adults), and 3.40 (seniors) mg/(kg×day). Risk assessment of median HI with respect to POPs indicated no risk (HI <1) for people in adolescents, adults, and seniors in the country area of China, while a risk (1 < HI < 10) would refer to the baked food consumption of people in urban area and children in country area of China. Sensitivity and uncertainty analysis showed that the most significant variables for each age group in China were POP concentration, body weight, and ingestion rate.